FECAL METABOLOMIC ANALYSIS OF SERT DEFICIENT MICE UNDER BASAL CONDITIONS AND CHRONIC COLITIS. (21st January 2021) - Sharma, Anchal; Qazi, Aisha; Priyamvada, Shubha; Kumar, Anoop; Ceh, Justin; Bhalala, Jeet; Alrubaee, Mohammed; Dudeja, Shreya; Weber, Christopher; Alrefai, Waddah; Saksena, Seema; Dudeja, Pradeep; et al.
Abstract: Inflammatory bowel diseases (IBDs) are chronic inflammatory multifactorial diseases caused by genetic, immune, and environmental factors. A decrease in intestinal serotonin transporter (SERT), which controls the extracellular availability of serotonin (5-HT) has been implicated in IBD. We previously showed that SERT deletion in mice altered gut bacterial community structure. The gut microbiota-derived metabolites are functional intermediaries between the microbiota and host. Here, we investigated the impact of SERT deficiency on gut metabolites under basal conditions and chronic colitis mimicking human IBD. Methods: Global metabolic profiles were analyzed by "Metabolon" (Durham, NC) on fecal samples from wild type littermates (WT) and SERT KO mice given water or chronic DSS (2.5% DSS for 5 weeks, n=7–9/group). Data were analyzed by ANOVA contrasts (difference between groups) and by two-way ANOVA (P<0.05, q<0.01). Results: SERT KO exhibited more severe colitis vs WT as assessed by histological score, myeloperoxidase activity and colon length. There was more pronounced decrease in the mRNA of tight junction proteins (TJs) occludin-1 and ZO-1 in SERT KO DSS vs WT DSS intestine. Metabolic profiling revealed that SERT deficiency alone resulted in extremely low levels of fecal ectoine, a bacterial derived solute that maintains TJ proteins expression. DSS treatment of WT (but not SERT KO) resulted in a significant increase in microbial derived metabolites including phenylalanine, N-acetylphenylalanine, tyrosine derivatives, glutamate, glutamine and benzoate derivatives . An increase in Trimethylamine N-oxide (TMAO ), the short chain fatty acids butyrate/isobutyrate, TCA cycle metabolites; and a decrease in several metabolites including spermidine and various primary and secondary bile acids occurred in DSS treated WT and SERT KO to varying degrees; suggesting that these pathways may contribute to the colitis severity in SERT KO mice. Several secondary bile acids, ketone bodies, the metabolites of pterin, riboflavin pathway (FAD and FMN) and fatty acid metabolism pathways were increased in SERT KO (basal and DSS) suggesting genotype related differences in microbial community. We recently showed an impairment of Aryl hydrocarbon receptor (AhR), an IBD susceptible gene, in SERT KO mice, which could be partly due to altered availability of ligands. Indeed, the bacterial derived AhR ligand tryptamine was extremely low in SERT KO (basal and DSS). DSS increased the host derived AhR ligand, kynurenine in WT, but not in SERT KO. Conclusion: These data highlight the impact of serotonergic machinery and SERT inhibition on host physiology and pathophysiology of IBD. The results provide unique insights into gut bacteria derived metabolites and may aid in the development of novel treatment for disorders with altered SERT and 5-HT availability (Supported by CCFA and NIH).